Sentinel event in oral health: experience with children with up to six years of age, users of the Unified Health System - Nora Nei Reis PEREIRA; Saul Martins PAIVA; Eliana Maria de Oliveira SÁ; Rafaela da Silveira PINTO; Simone Dutra LUCAS (Faculdade São Leopoldo Mandic, 2018)
Objective: The aim of this study was to find out the children's profile identified as Sentinel Event in oral health by the Municipal Health Department of the city of Belo Horizonte, State of Minas Gerais, Brazil. Methods: A quantitative, analytical, exploratory and documentary analysis study was developed in the city of Belo Horizonte, State of Minas Gerais, Brazil, involving 545 children, age ranging from zero to six years old. Sentinel event data were collected through an electronic form created in the Unified Health System and filled out by the municipal oral health teams. Information systems of the city council were consulted. The variables studied were as follows: Health Vulnerability Index, race/color, age, sex, to be beneficiary of the Bolsa Família Program (a social program sponsored by the government), to be monitored by the Strategy of the Family Health Program, to reside in the Belo Horizonte Citizenship Program area, nature of the school and region of residence. Statistical analysis was performed in the SPSS software, 20th version. Results: The results showed that the majority of children live in areas of medium and high social risk, they are five to six years old, male, dark-skinned, do not benefit from the Bolsa Família program, are not under the Strategy of the Family Health Program, do not reside in the territory of the Belo Horizonte Citizenship Program, and study in institutions of the municipal education network. The sentinel event is present in the nine regions of Belo Horizonte, with a higher prevalence in the regions of Venda Nova, Northeast, West, East and Barreiro. Conclusion: The study demonstrates the crucial importance of comprehensive social policies in order to influence oral health.